Theoretical and empirical issues in tourism demand analysis - De Mello, Maria M.M.Q. (2001)
The majority of empirical studies of tourism analysis use a static single equation approach to model the demand for tourism of one origin for one or more destination countries. The examination of such studies generally shows that the economic interpretation and policy implications drawn as conclusions are based on mis-specified models, invalid estimation and inference procedures, inconsistent estimates and poor forecasting performance. Static single equation models of tourism demand tend to neglect interdependencies among destinations, ignore nonstationarity, overlook dynamics and, generally, disregard economic theory. Empirical specifications constrained by these flaws are bound to generate biased and inconsistent estimates upon which no reliable economic analysis or policy implication can be based.